PENGARUH MODEL PREDICT-OBSERVE-EXPLAIN (POE) TERHADAP KEMAMPUAN BERPIKIR KREATIF SISWA PADA MATERI LARUTAN ELEKTROLIT DAN NON ELEKTROLIT (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This study aims to examine the extent to which the application of the Predict-Observe-Explain (POE) model has a significant effect on students' creative thinking skills on the topic of electrolyte and non-electrolyte solutions. Using a quasi-experimental approach with a Pretest-Posttest Nonequivalent Control Group design, which describes the causal relationship between variables. The sample was selected randomly, with the experimental class applying the POE model and the control class using the CPS learning approach. The research instruments included creative thinking observation sheets, student activities, and teacher activities, while data analysis was carried out using the t-test. The results of the creative thinking observation showed that the average creative thinking score of the control class was 51.42, which is in the fairly good category, while the experimental class obtained an average of 54.53 with the same category. When viewed based on the results of observations of student activities, it shows that the average creative thinking score of the control class was 67.74, which is in the good category, while the experimental class obtained an average of 68.33, which is in the good category. Data were analyzed using the t-test, after previously conducting normality and homogeneity tests. The test results show that there is a significant difference between the two classes, indicated by the t-count value which is greater than the t-table, namely 2.77 > 1.67.